MRI-based morphological evidence of spinal cord tethering predicts curve progression in adolescent idiopathic scoliosis - Deng, Min; Hui, Steve C.N.; Yu, Fiona W.P.; Lam, Tsz-Ping; Qiu, Yong; Ng, Bobby K.W.; Cheng, Jack C.Y.; Chu, Winnie C.W. (The spine journal, 2015)
Existing prognostic factors for adolescent idiopathic scoliosis (AIS) patients have focused mainly on curve, maturity, and bone-related factors. Previous studies have shown significant associations between curve severity and morphological evidences of relative shorter spinal cord tethering in AIS, and increased prevalence of abnormal somatosensory cortical–evoked potentials and low-lying cerebellar tonsil in severe AIS. Earlier evidence suggests that there might be neural morphological predictors for curve progression. The purpose of this study was to identify any morphological predictors associated with cord tethering, as measured by magnetic resonance imaging (MRI), for curve progression in AIS patients. This is a prospective cohort study. A total of 81 female AIS subjects between 10 and 14 years were included, without surgical intervention during the follow-up period. Magnetic resonance imaging scans of hindbrain and whole spine and areal bone mineral density (BMD) at bilateral femoral necks were performed. All AIS patients were longitudinally followed up starting from initiation of bracing beyond skeletal maturity in 6-month intervals. Clinical and radiographic data were recorded at each clinic visit. Bone mineral density and MRI measurements including ratio of spinal cord to vertebral column length, ratio of anteroposterior (AP) and transverse (TS) diameter of cord, lateral cord space (LCS) ratio, cerebellar tonsil level, and conus medullaris position were obtained at baseline. Only compliant patients with a minimum 2-year follow-up were analyzed. Adolescent idiopathic scoliosis girls were assigned into three groups according to bracing outcome: Group A, nonprogression (curvature increase of less than or equal to 5°); Group B, progression (curvature increase of greater than or equal to 6°); Group C, progression with surgery indication (Cobb angle of greater than or equal to 50° after skeletal maturity despite bracing). The predictors for curve progression were evaluated using univariate analysis and multivariate ordinal regression model. The average duration of follow-up was 3.4 (range, 2.0–5.6) years. There were 46 girls (57%) in Group A, 19 (23%) in Group B, and 16 (20%) in Group C. No significant intergroup differences were found in spinal cord length, tonsil level, and conus position. Group C had significantly longer vertebral column length, smaller cord-vertebral length ratio, and higher AP/TS cord ratio compared with Group A, whereas LCS ratio in Group C was significantly increased compared with both Group A and Group B. In regression model, five significant independent predictors including cord-vertebral length ratio (odds ratio [OR]: 1.993 [95% confidence interval CI: 1.053–3.771], p=.034), LCS ratio (OR: 2.639 [95% CI: 1.128–6.174], p=.025), initial Cobb angle (OR: 1.156 [95% CI: 1.043–1.281], p=.006), menarche age (OR: 1.688 [95% CI: 1.010–2.823], p=.046), and BMD (OR: 2.960 [95% CI: 1.301–6.731], p=.010) and a marginally significant predictor namely AP/TS cord ratio (OR: 1.463 [95% CI: 0.791–2.706], p=.096) were obtained. On baseline MRI measurement, cord-vertebral length ratio and LCS ratio are identified as new significant independent predictors for curve progression in AIS, whereas AP/TS cord ratio is suggested as a potential predictor requiring further validations. The earlier MRI parameters can be taken into accounts for prognostication of bracing outcome.